2022
DOI: 10.3390/hydrology9120225
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Rain Gauge and Weather RaDAR Data in the Estimation of the Pluviometric Inflow from the Apennine Ridge to the Adriatic Coast (Abruzzo Region, Central Italy)

Abstract: Accurate knowledge of the rain amount is a crucial driver in several hydrometeorological applications. This is especially true in complex orography territories, which are typically impervious, thus, leaving most mountain areas ungauged. Due to their spatial and temporal coverage, weather radars can potentially overcome such an issue. However, weather radar, if not accurately processed, can suffer from several limitations (e.g., beam blocking, altitude of the observation, path attenuation, and indirectness of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…For example, Schleiss et al [69] found a underestimation of radar data compared to rain gauge of 10% in a study over northern Europe. Di Curzio et al [70] also found a general underestimation in Abruzzo and Marsica regions in Italy. In contrast, the overestimation signal estimated over the JUR area tended to be linked with the contribution of the German radars.…”
Section: Discussionmentioning
confidence: 88%
“…For example, Schleiss et al [69] found a underestimation of radar data compared to rain gauge of 10% in a study over northern Europe. Di Curzio et al [70] also found a general underestimation in Abruzzo and Marsica regions in Italy. In contrast, the overestimation signal estimated over the JUR area tended to be linked with the contribution of the German radars.…”
Section: Discussionmentioning
confidence: 88%
“…Also, the traditional approach could benefit from a higher number of point data. The recent developments obtained with the use of weather RaDAR data are encouraging [9,39,40] and may represent a valuable additional source of information to be integrated into the water budget estimation, especially through an advanced geostatistical approach (e.g, Multi-Collocated Co-Kriging or Kriging with External Drift). The use of weather RaDAR data would allow estimating in a more reliable way the spatial distribution of rainfall on a finer grid mesh and with a lower associated uncertainty.…”
Section: Comparison Between Traditional and Geostatistical Methodsmentioning
confidence: 99%
“…Errors in the data may result from many factors, such as disturbance of the radar signal by buildings or terrain, and technological limitations. Therefore, in recent years, many researchers have sought to combine two or three of these datasets in order to maximize the advantages and minimize the disadvantages [95,96].…”
Section: Issues Related To Flood Simulationsmentioning
confidence: 99%